Strategi Adaptasi Sistem Penjaminan Mutu Pendidikan Islam di Era Disrupsi Digital - Nugraha, Mulyawan Safwandy; Mudriansah, Asep Septian; Alih, Deni; Widianengsih, Rina; Aisyah, Yesi Siti (Penerbit Widina, Widina Media Utama, 2025)
The disruption era marked by rapid advancements in digital technology demands that education systems, including Islamic education, adapt quickly and effectively. This article analyzes the adaptation strategies of the Islamic education quality assurance system in facing disruption challenges using a qualitative approach through literature review. The findings reveal that Islamic educational institutions implement digitalization of quality assurance instruments and processes, strengthen human resource competencies through continuous training, optimize the use of information technology in management, and enhance cross-institutional collaboration. Additionally, policy adjustments play a crucial role in ensuring flexibility and sustainability of education quality. These adaptive and innovative responses are key to maintaining the relevance and quality of Islamic education in the disruption era. This study offers practical contributions for developing policies and operational strategies for Islamic education quality assurance that are more responsive to changing times.ABSTRAKEra disrupsi yang ditandai dengan kemajuan teknologi digital menuntut sistem pendidikan, termasuk pendidikan Islam, untuk beradaptasi secara cepat dan efektif. Artikel ini menganalisis strategi adaptasi sistem penjaminan mutu pendidikan Islam dalam menghadapi tantangan disrupsi dengan pendekatan kualitatif melalui studi pustaka. Temuan menunjukkan bahwa lembaga pendidikan Islam mengimplementasikan digitalisasi instrumen dan proses penjaminan mutu, memperkuat kompetensi sumber daya manusia melalui pelatihan berkelanjutan, mengoptimalkan pemanfaatan teknologi informasi dalam tata kelola, serta meningkatkan kolaborasi lintas lembaga. Selain itu, penyesuaian kebijakan menjadi aspek penting untuk menjamin fleksibilitas dan keberlanjutan mutu pendidikan. Respons adaptif dan inovatif ini menjadi kunci utama dalam menjaga relevansi dan kualitas pendidikan Islam di era disrupsi. Penelitian ini memberikan kontribusi praktis bagi pengembangan kebijakan dan strategi operasional penjaminan mutu pendidikan Islam yang lebih responsif terhadap dinamika zaman.